Implementation of RSA Cryptography Algorithm in Data Encryption for Location Manipulation Based on IP Address - Harahap, Muhammad Bintang; Amrullah (PT. Technology Laboratories Indonesia (TechnoLabs), 2024)
This research enhances data security for geolocation information derived from IP addresses using RSA encryption. In today’s digital era, protecting sensitive data is crucial, as personal information is often transferred and stored electronically. Encryption is a key security method that transforms readable data (plaintext) into unreadable code (ciphertext) without the correct decryption key, thereby safeguarding it from unauthorized access. The RSA algorithm, specifically with a 2048-bit key length, has proven effective in securing geolocation data against brute-force attacks, ensuring that only authorized users with the correct decryption key can access the information. This study confirms that RSA encryption allows encrypted geolocation data to be stored safely in databases, maintaining data confidentiality and integrity. Ultimately, this research contributes to the understanding of RSA cryptography's application in data encryption for IP-based location data, offering a reliable method to prevent data manipulation and unauthorized access.